Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

pH Buffering in Stormwater Infiltration Systems—Sustainable Contaminant Removal with Waste Mussel Shells - J. F. Good; A. D. O’Sullivan; D. Wicke; T. A. Cochrane (Water, Air, & Soil Pollution, 2014)

Changes in angler participation and demographics: analysis of a 17‐year licence stub return system for Atlantic salmon - J. B. DEMPSON; M. J. ROBERTSON; N. M. COCHRANE; M. F. O’CONNELL; G. PORTER (Fisheries Management and Ecology, 2012)
Patterns of change in angler participation and demographics were examined for the recreational Atlantic salmon, Salmo salar L., fishery in Newfoundland and Labrador, Canada. An analysis of a licence stub return system, 1994–2010, showed a significant decline in resident angler participation, but this was not consistent across all regions of the Province. Mean age of anglers increased significantly, varying from 39.0 years in 1994 to 46.5 years by 2010. In some regions, mean age rose by over 12 years since the mid‐1990s, reflecting a decline in the recruitment of younger anglers. The return rate of angler logs also declined over time and was found to vary by age, sex and area of angler residence. Women and older anglers, and those living in specific rural areas had a greater tendency to return a record of their catch history than men and younger anglers. Identified changes in participation and demographics, which can affect exploitation and ultimately abundance, could be used to develop management measures that would maximise both harvest and socio‐economic benefits to the varied users of the resource.

Degradation of Connexins Through the Proteasomal, Endolysosomal and Phagolysosomal Pathways - Vivian Su; Kimberly Cochrane; Alan F. Lau (The Journal of Membrane Biology, 2012)

A Smart Market for Impervious Cover - John F. Raffensperger; Thomas A. Cochrane (Water Resources Management, 2010)

Benguela Current Large Marine Ecosystem—Governance and Management for an Ecosystem Approach to Fisheries in the Region - K. L. Cochrane; C. J. Augustyn; T. Fairweather; D. Japp; K. Kilongo; J. Iitembu; N. Moroff; J. P. Roux; L. Shannon; B. Van Zyl; F. Vaz Velho (Coastal Management, 2009)

The regional variation of aboveground live biomass in old‐growth Amazonian forests - YADVINDER MALHI; DANIEL WOOD; TIMOTHY R. BAKER; JAMES WRIGHT; OLIVER L. PHILLIPS; THOMAS COCHRANE; PATRICK MEIR; JEROME CHAVE; SAMUEL ALMEIDA; LUZMILLA ARROYO; NIRO HIGUCHI; TIMOTHY J. KILLEEN; et al. (Global Change Biology, 2006)
The biomass of tropical forests plays an important role in the global carbon cycle, both as a dynamic reservoir of carbon, and as a source of carbon dioxide to the atmosphere in areas undergoing deforestation. However, the absolute magnitude and environmental determinants of tropical forest biomass are still poorly understood. Here, we present a new synthesis and interpolation of the basal area and aboveground live biomass of old‐growth lowland tropical forests across South America, based on data from 227 forest plots, many previously unpublished. Forest biomass was analyzed in terms of two uncorrelated factors: basal area and mean wood density. Basal area is strongly affected by local landscape factors, but is relatively invariant at regional scale in moist tropical forests, and declines significantly at the dry periphery of the forest zone. Mean wood density is inversely correlated with forest dynamics, being lower in the dynamic forests of western Amazonia and high in the slow‐growing forests of eastern Amazonia. The combination of these two factors results in biomass being highest in the moderately seasonal, slow growing forests of central Amazonia and the Guyanas (up to 350 Mg dry weight ha −1 ) and declining to 200–250 Mg dry weight ha −1 at the western, southern and eastern margins. Overall, we estimate the total aboveground live biomass of intact Amazonian rainforests (area 5.76 × 10 6 km 2 in 2000) to be 93±23 Pg C, taking into account lianas and small trees. Including dead biomass and belowground biomass would increase this value by approximately 10% and 21%, respectively, but the spatial variation of these additional terms still needs to be quantified.

Introduction - William F. Laurance; Mark A. Cochrane (Conservation Biology, 2001)

Potential impact of climate warming on recreational fishing opportunities for Atlantic salmon, Salmo salar L., in Newfoundland, Canada - J. B. Dempson; M. F. O'Connell; N. M. Cochrane (Fisheries Management and Ecology, 2001)
Potential impacts of climate warming on recreational fishing opportunities were addressed by assessing the frequency and extent that Atlantic salmon, Salmo salar L., rivers in Newfoundland have been closed over a 25‐year period (1975 to 1999) because of warm water temperatures and low water levels. On average, approximately 28% of all salmon rivers were temporarily closed annually, with over 70% affected in some years. This has resulted in a loss of 35–65% of the potential fishing days available in some salmon fishing areas with the collective 1995 to 1999 period being impacted the most over the past two decades. Geographically, west and south‐west coastal rivers were affected less from environmental closures than east and some south coast fishing areas. A trend for increased closures of rivers related to environmental reasons could reduce the economic importance of the recreational salmon fishery and also make it more difficult to assess the status of Atlantic salmon stocks, which is a requirement for conservation of the resource.